The Transformation of Social Contract Theory: From Classical Natural Law Theory to the Individual of Liberalism - Ebinç, Sait (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This article aims to analyze how classical Natural Law Theory in the 17 th century underwent a philosophical and epistemological transformation to become the foundational theory of the modern state in 17th century Europe. One of the primary focuses of this analysis is on exploring the historical societal processes and phenomena resulting from the principles of the Theory of Natural Law, particularly the theories of social contract. Another pivotal aspect of this scrutiny involves analyzing the relationship between individual-reason-nature, grounded in Liberalism’s Theory of Natural Law, by comparing perspectives on Natural society and symbolic society. In a sense, this article aims to bridge distant and recent history, creating a short circuit to analyze the changes and transformations within the Theory of Natural Law.